Cinemática escapular 3-D e ativação muscular em indivíduos com hemiparesia crônica : implicações para a reabilitação do membro superior pós-AVE - Lixandrão, Maíra Carolina (2017)
Background: Stroke can lead to bilateral shoulder and scapular movement and muscle activation impairments that can limit the ability to perform activities of daily life (ADLs). Aims: To evaluate scapular kinematics and shoulder muscle activation in individuals with chronic stroke and its correlation to paretic arm use. Methods: Scapular kinematics and muscle activation of upper trapezius (UT), lower trapezius (LT), serratus anterior (AS), anterior deltoid (AD) and middle deltoid (MD) from 17 individuals post-stroke and 17 controls were evaluated during arm elevation and lowering in scapular and self-selected planes, and during hair combing. Paretic arm use was assessed using the Motor Activity Log (MAL-30). The scapular kinematics and muscle activation (amplitude and onset/offset) were compared among arms and groups using a two-way mixed model ANOVA. The scapular kinematics and muscle activation were correlated to MAL-30 using the Spearman correlation test. Significant p value was set at <0.05. Results: Kinematics: Paretic and non-paretic arms showed increased scapular internal rotation during arm lowering in the scapular plane, and during arm elevation and lowering in the self-selected plane compared to controls. Increased internal rotation was also found in the paretic arm during hair combing compared to controls. Increased scapular anterior tilt was observed in the paretic arm during arm elevation while performing the activity of hair combing and during arm elevation and lowering in the scapular and self-selected planes compared to controls. The non-paretic arm showed increased anterior tilt during arm elevation and lowering in self-selected plane compared to controls. Muscle activation: Compared to controls, the paretic and non-paretic arms presented decreased LT and MD activation during arm elevation in all planes, and decreased AD activation during arm elevation in scapular plane. Both arms of post-stroke group presented decreased LT activation during arm lowering in scapular and self-selected planes, and delayed MD activation during arm lowering in self-selected plane and to comb their hair. Paretic and non-paretic arms showed delayed SA, UT and LT onset in self-selected plane. The paretic arm also presented delayed onset of these muscles during hair combing compared to controls, and a delayed UT offset in self-selected plane compared to LT and SA. All groups presented delayed SA onset in scapular and self-selected planes, compared to UT. Scapular kinematic and muscle activation alterations were not correlated to paretic arm use. Conclusions: Individuals with chronic stroke showed bilateral alterations in scapular kinematics and shoulder muscle activation. However, these alterations are not correlated to paretic arm use.